MANAJEMEN PERAWATAN DENGAN MENGGUNAKAN PSIKOEDUKASI BERBASIS KOMPUTER TERHADAP KLIEN DEPRESI RINGAN - Zaini, Mad (E-Journal Widya Kesehatan dan Lingkungan, 2014)
Depression care management on the client depending on psychotherapy, pharmacotherapy, and education client’s. Implementation of the psychoeducation computer based collaborate between models of depression care management on the client with computer media. The objective of this study are: to discuss the psychoeducation computer based, (2)to determine the effectiveness of psychoeducation computer based on client’s with low depression. The method used is literature research with descriptive and explorative approach. It can be concluded that: (1) care management on client with low depression by computers based can increasing the ability client's to understand problem, repair the coping mechanism. (2) using the computer based media on the care management client’s with low depression can increasing motivation and interest to depression treatment programe.